2008
DOI: 10.1007/s10342-008-0204-z
|View full text |Cite
|
Sign up to set email alerts
|

Field measures of the contribution of root respiration to soil respiration in an alder and cypress mixed plantation by two methods: trenching method and root biomass regression method

Abstract: The contribution of root respiration to total soil respiration is one of the most interesting, important, and methodologically complicated problems in the study of the carbon budget in soils. A trenching method and a root biomass regression method were used to determine the contribution of root respiration to total soil respiration in a subtropical forest ecosystem. The average root respiration contributions were 37.15% with the range of 13.04-51.23% by trenching method and 31.80% with the range of 10.64-56.10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…The R r was separated from R ff by subtracting trenched plots' respiration from that of control plots at a black spruce forest in Quebec by Hermle et al (2010), and R r was found to be 24 % of R ff . However, the R r percentage was found to be higher (37 %) in a subtropical forest of mixed alder and cypress plantation (Wang et al, 2008) in a similar trenching experiment. Hanson et al (2000) have reported even higher mean root and rhizomicrobial respiration values of 46 and 60 % for forest and nonforest vegetation, respectively.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…The R r was separated from R ff by subtracting trenched plots' respiration from that of control plots at a black spruce forest in Quebec by Hermle et al (2010), and R r was found to be 24 % of R ff . However, the R r percentage was found to be higher (37 %) in a subtropical forest of mixed alder and cypress plantation (Wang et al, 2008) in a similar trenching experiment. Hanson et al (2000) have reported even higher mean root and rhizomicrobial respiration values of 46 and 60 % for forest and nonforest vegetation, respectively.…”
Section: Introductionmentioning
confidence: 96%
“…While the trenching is used to separate R r from R ff , it also adds fresh litter to the peat that can add to the initial heterotrophic soil respiration. However, it has been assumed in trenching experiments that the trenched roots die off within a short time and that afterwards the measured R ff can solely be attributed to heterotrophic soil respiration (Hanson et al, 2000;Hermle et al, 2010;Wang et al, 2008). Trenching immediately disrupts the supply of recent photosynthates to the roots and mycorrhiza and associated bacteria that suffer from the lack of labile C. In trenching experiments Bowden et al (1993), Boone et al (1998) and Rey et al (2002) have shown that C content of decomposing fine roots in trenched plots contributed little to R r and becomes stable a few months after trenching.…”
Section: T M Munir Et Al: Carbon Dioxide Flux and Net Primary Prodmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there are methodological difficulties in separating respiration sources (Hanson et al 2000;Subke et al 2006), one practical method to estimate root respiration is to dig a trench around the respiration monitoring chamber in order to exclude root respiration from the soil (Katagiri 1988;Lee et al 2003;Sulzman et al 2005;Vogel et al 2005, Wang et al 2006Schaefer et al 2009). The root trenching method in particular is often used in the forest ecosystem because of its high applicability to remote areas despite criticisms that disturbance by trenching affects root decomposition, soil moisture, and the soil microbial community (Hanson et al 2000;Kuzyakov and Larionova 2005).…”
Section: Introductionmentioning
confidence: 99%